Search Costs and the Determinants of Job Search - Emily A. Beam (Institute of Labor Economics (IZA), 2020)
This paper examines how individuals select into job search in terms of their individual qualifications and perceptions and measures how recruiting additional applicants with a modest job-search subsidy affects selection. I use experimental evidence to examine individuals' decisions to attend and participate in a job fair. Thirteen percent of invited but unsubsidized respondents attend the job fair, and they are positively selected from the overall distribution of respondents. While the subsidy attracts those who are less qualified and less confident in their ability to find work abroad, the least qualified do not search intensively. Although the subsidy does not lead to any additional offers, it induces individuals with a high degree of uncertainty about their likelihood of job-finding to apply with recruitment agencies. These results demonstrate the importance of imperfect information about the returns to search and highlight how reducing search costs can increase search effort among those most uncertain about their prospects.
Keywords: O15; J64; D83; C93; 330; recruitment; job search; perceived returns; migration; field experiment